2023
DOI: 10.3390/cells12091331
|View full text |Cite
|
Sign up to set email alerts
|

“Combo” Multi-Target Pharmacological Therapy and New Formulations to Reduce Inflammation and Improve Endogenous Remyelination in Traumatic Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is characterized by a cascade of events that lead to sensory and motor disabilities. To date, this condition is irreversible, and no cure exists. To improve myelin repair and limit secondary degeneration, we developed a multitherapy based on nanomedicines (NMeds) loaded with the promyelinating agent triiodothyronine (T3), used in combination with systemic ibuprofen and mouse nerve growth factor (mNGF). Poly-L-lactic-co-glycolic acid (PLGA) NMeds were optimized and loaded with T3 to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Journal of Inflammation Research 2023:16 4766 and creating the final chronic stage scar. 31,[66][67][68] The body's natural process of glial scar formation, which initiates and initiates healing after SCI, but some researchers believe it to be one of the barriers to neuronal axon regeneration in the CNS (central nervous system). [69][70][71] Lesions grow and create cysts as the spinal cord injury progresses, leaving behind microcystic cavities from lingering necrotic or apoptotic cells that eventually form spinal cord cavities, inflicting permanent harm.…”
Section: Dovepressmentioning
confidence: 99%
“…Journal of Inflammation Research 2023:16 4766 and creating the final chronic stage scar. 31,[66][67][68] The body's natural process of glial scar formation, which initiates and initiates healing after SCI, but some researchers believe it to be one of the barriers to neuronal axon regeneration in the CNS (central nervous system). [69][70][71] Lesions grow and create cysts as the spinal cord injury progresses, leaving behind microcystic cavities from lingering necrotic or apoptotic cells that eventually form spinal cord cavities, inflicting permanent harm.…”
Section: Dovepressmentioning
confidence: 99%
“…In fact, our and other groups have demonstrated that OPC differentiation/maturation impairment in experimental allergic encephalomyelitis (EAE), an experimental model for MS, is accompanied by an increase in the T3-inactivating enzyme deiodinases 3 (D3) and dysregulation of TR mRNA expression [ 22 , 23 , 24 ]. We have also demonstrated that inflammation-induced tissue hypothyroidism can be partially overcome in vivo by exogenous T3 administration, observing that OPC differentiation and maturation are restored in T3-treated animals, resulting in improved myelin repair in EAE [ 22 ] and SCI [ 25 ]. This result has been confirmed by in vitro experiments in which we have demonstrated that inhibition of inflammation-induced D3 hyperactivity restores OPC differentiation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%